Safety and Efficacy of Adjunctive Balloon Remodeling during Endovascular Treatment of Intracranial Aneurysms: A Literature Review - Shapiro, M.; Babb, J.; Becske, T.; Nelson, P.K. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Concurrent temporary inflation of a nondetachable balloon in the parent artery has been reported to be useful during endovascular coiling of complex, wide-neck aneurysms, facilitating truer coil reconstruction of the native vessel. Nevertheless, there exists concern that adjunctive use of balloon assistance may lead to increased adverse events during aneurysm coiling.MATERIALS AND METHODS: A literature search of all of the unassisted and balloon-remodeling studies published between 1997 and 2006 was conducted with application of strict selection criteria based on the reporting of complication incidence and outcome. The final cohort was analyzed to determine rates and clinical outcomes of iatrogenic aneurysm rupture and thromboembolism. Additional data were collected on the degree of initial and follow-up aneurysm occlusion rates.RESULTS: A total of 83 potential studies (4973 patients) were identified, from which 23 articles reporting results for 867 traditional-unassisted and 273 balloon-assisted coiled aneurysms met inclusion criteria for the analysis of thromboembolic complications, and 21 articles with 993 routinely coiled and 170 balloon-remodeled aneurysms were eligible for iatrogenic perforation analysis. No statistically significant difference was found in the rates of thromboembolism. Iatrogenic perforation rates were also comparable, though the overall numbers were too few for meaningful statistical analysis. Both initial and follow-up aneurysm occlusion rates were higher in balloon-assisted cases.CONCLUSION: This largest-to-date literature review and meta-analysis did not demonstrate a higher incidence of thromboembolic events or iatrogenic rupture with the use of adjunctive balloon remodeling compared with unassisted coiling. Balloon remodeling appears to result in higher initial and follow-up aneurysm occlusion rates.